Economic Digitalization of Tourism Village in The New Normal Era (Case Study in Pipitan Tourism Village) - Sugeng Setyadi; Rizal Syaifudin (MOVE: Journal of Community Service and Engagement, 2022)
The purpose of this community service is to provide appropriate technology in the form of an official website, training in the preparation of interesting social media content for marketing, as well as training in making digital-based financial reports in Pipitan Tourism Village, Serang City. Pipitan Tourism Village is a Tourism Village that was formed in 2019 with the establishment decision letter number 821/25 of 2020 concerning the Designation of Pipitan Tourism Village from the Serang City tourism office. However, the COVID-19 pandemic has made this tourist village empty of visitors. For this reason, in the new normal, a strategy is needed on how to bring back tourist visits to Pipitan Tourism Village, including through digital marketing, namely through the official website which is currently not owned. The second strategy is to rearrange the content on social media to make it more interesting so that it can have a selling value. In addition, the recording of financial reports conducted by Pokdarwis is also still simple and done manually and not in accordance with the ETAB standard, so training is needed on how to prepare financial reports that comply with ETAB standards and are digitally based.